Public communication for handling Hoax about Covid-16 vaccine: A content analysis on official social media of Ministry of Communications and Informatics, Indonesia - Tongat; Salahudin, Salahudin (Technium Social Sciences Journal, 2024)
There have been many victims of the circulation of hoaxes about the Covid-19 vaccine, especially for people with low literacy capacity. The impact is the community’s non-compliance to carry out vaccinations. Thus, this research was carried out with the aim of knowing how the role and process of managing Twitter social media belonging to the Ministry of Communications and Informatics are through published content in order to stem hoaxes about the Covid-19 vaccine. This research was carried out using a qualitative descriptive method with the help of the Nvivo 12 Plus software application and utilizing the Ncapture feature, which is considered effective in helping qualitative research efficiently. This study reveals that the Indonesian government actively uses Twitter as a means of communication to control the spread of hoaxes about the Covid-19 vaccine, which is indicated by the high intensity of postings, actor involvement and relations, narratives, and education related to information and disinformation about the Covid-19 vaccine.This research contributes to the hoax handling strategy through social media that can be implemented through government policies and programs. In addition, this study also illustrates that the study of communication about hoaxes on social media can be carried out systematically through the use of social media data with analysis using content analysis applications such as NVivo 12 Plus.